Chapter 2: One, two, many ways – a hands-on guide to how to navigate this book - Mayrhofer, Wolfgang; Briscoe, Jon; Dickmann, Michael; Hall, Douglas T.; Parry, Emma (Edward Elgar Publishing, 2023)
This book contains career stories in context from all the populated continents in the world. It demonstrates how to look at careers from various perspectives. The stories are grouped in to 6 key themes: personal characteristic, stability and change, boundaries and borders, gender, generations and organizations. the chapters commence with a point of departure that sets the scene, constitutes a dilemma or problem or the like before contextualizing the situation. This usually is done by a brief introduction to the country and its specifics with regard to the careers and the core of the emerging story. Reflections on the story point towards core issues and related theoretical discourses. ‘Stop and Think’ sections with a few questions intended to stimulate further thoughts about the story close the chapter and are geared to produce relevant take-aways for the reader.